Le maire et la mosquée. Islam et laïcité en Île de France - Françoise Duthu (L’Année du Maghreb)
Numerous politicians and media outlets in France have been developing a discourse that vilifies Muslims and the Islamic faith when commenting on national or international events. Surprisingly, many decisions concerning the way Muslims practice their faith are in fact decided on the municipal level. Mayors in France are confronted with a new situation in which Muslim populations have become active citizens and their towns are now faced with developing a “municipal policy towards the Islamic faith”. The building or renovation of mosques or religious prayer rooms has become central in structuring the relationship between mayors and fellow Muslim citizens. Whether a mayor’s political tendency is of the left or the right is less important than the representations political leaders may have of Islam and secularism. It is time that society should organize a public debate concerning differential treatment of the Muslim religion and that finally, according to the principals of secularism in French society, Muslims should be assured of genuine equality in their religious practices throughout the Republic.